An Examination of Differentially-Expressed Genes from Oil Palm Embryogenic and Non-Embryogenic Cultures - Ooi, Siew Eng (2003)
To date the embryogenesis rate in oil palm tissue culture averages 6%. Thus, there is a need to find ways to increase this rate and also to create a selection system that is able to distinguish embryogenically competent calli from their non-embryogenic counterpart at an early stage. Using cold plaque screening of oil palm suspension cultures, about 1000 clones were isolated. About sixty-four percent of the clones have extremely low expression levels in suspension cultures and non-embryogenic calli. Another 22% were found to be up-regulated in suspension cultures compared to non-embryogenic calli. Out of the 600 sequenced clones, 46% were found to be novel or similar to proteins with unknown functions. Most of the other genes were found to be involved in cell metabolism and proliferation, which leads to an increase in the expression of genes involved in namely, protein synthesis and signal transduction pathways. cp919.1, a TUBBY-like protein homolog or a similar member of the TULP family is up-regulated in non-embryogenic callus. cp 194.2, a member of a novel serine/threonine kinase subfamily, is up-regulated in embryogenic callus. As hypothesized in the mammalian systems, cp194.2 may play a role in the disruption of the extracellular matrix surrounding the proembryogenic masses. Transcripts of cp664.2, a truncated leucine-rich-repeat encoding protein and cp610.2, a HD-Zip II gene were up-regulated in suspension cultures. The role of cp610.2 is unknown, but it may be involved in the transcription of genes involved in early embryogenesis. 3N42.2 was isolated by RT-PCR followed by cDNA library screening. 3N42.2, a NAC superfamily member, like CUCI/2 may be expressed in the presumptive shoot apical meristem of the embryos and then be restricted to the boundary regions of the apical meristem at later embryogenic stages. 3N42.2 expression then remains at the boundary regions of the meristem during post-embryonic development. cp194.2, cp610.2 and 3N42.2 may be used as markers for early somatic embryogenesis. Functional elucidation needs to be carried out to understand the roles that these proteins play in plant development.